Renewable sources to promote well-being in poor regions of Brazil - Filho, Aloısio S. Nascimento; Borges, Toni; Salvador, Hugo; Ferreira, Paulo; Saba, Hugo (Frontiers in Physics, 2022)
Fossil fuels as a primary source have affected the environmental balance, with the effects being more intense in poor regions of the planet. The good news is that the 21st century has witnessed intensified efforts to use clean energy sources capable of competing with fossil fuels. An additional concern is to combine energy sustainability and socioeconomic well-being. Intensified use of renewable energy in poor regions may create opportunities for new businesses and jobs. The intensive use of alternative technologies in the energy matrix may generate new jobs in poor regions. Biomass, solar energy, and wind energy are examples of renewable sources in countries such as Brazil. This research aims to characterize the features of the energy matrix suitable for the different regions of Brazil and match optimal points for the implementation of micro-electric power plants for generation, distribution, and storage from renewable energy sources. This is an opportunity to contribute to a cycle of regional economic growth from a sustainable perspective.